The Correlation of Social Support for Families with Hypertension in the Elderly in Gampong Baro, Peudada District, Bireuen Regency - Bukhari; Roslaini (Akademi Keperawatan Kesdam Iskandar Muda Lhokseumawe, 2021)
The biggest hope of the elderly is going to spend live time happily, but most of them experience the opposite. They have to live with the unhappiness and causing the uncomfortable feeling inside. The aim of the research is to determine the correlation between social support and the incidence of hypertension in the elderly in Baro Village, Peudada District, Bireuen Regency. This is descriptive research, with a sample of 75 elderly and the sampling technique is taken by total sampling. The results showed that the average elderly experienced hypertension with the following causes, 51 (68.0%) hypertension caused by informational support, 55 elderly (73.3%) hypertension caused by assessment support, 52 elderly (69.3%) hypertension caused by instrumental support, 53 elderly (70.7%) hypertension caused by emotional support, 55 elderly (73.3%) caused by elderly hypertension. The cause of hypertension in the elderly in Gampong Baro is due to family support factors. It is suggested to families for paying more attention to things that cause hypertension in the elderly and provide support both in terms of information, instrumental, emotional, and social support.